Nationalism in Hafez Ibrahim’s Diwan: A Literary Analysis - Dr. Abdul Saboor (Al-Qanṭara, 2023)
This article provides a detailed literary analysis of the national themes present in Hafez Ibrahim's Diwan, a collection of poetry that reflects his profound love for Egypt. The analysis explores Ibrahim's exploration of national identity, unity, the struggle for freedom, and socio-political critique within his poetry. The article examines how Ibrahim personifies Egypt as a beloved entity, emphasizing the importance of cultural heritage and historical legacy in shaping national identity. It also highlights Ibrahim's portrayal of the struggle for freedom, showcasing his depiction of Egypt's fight against colonialism and oppression. Furthermore, the article delves into Ibrahim's socio-political critique, focusing on his commentary on corruption, injustice, and societal divisions. The analysis emphasizes the call to unity and collective action present in Ibrahim's work, inspiring readers to rise above their differences and work towards a common destiny. Overall, this article sheds light on the significant national themes in Hafez Ibrahim's Diwan and highlights the enduring power of his poetry to evoke a sense of national pride and shape the discourse on Egypt's national identity.